Determinants of Firm Value: Perspectives of Free Cash Flow, Investment Opportunities, Managerial Ownership, and Opportunistic Behavior - Wahyu Wijayanto; Mustaruddin Mustaruddin; Nur Afifah (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
This study analyses the effects of free cash flow, investment opportunities, managerial ownership, and opportunistic managerial behaviour on firm value with firm size as a control variable. The research sample comprises 35 manufacturing companies listed on the Indonesia Stock Exchange for 2018-2022. Data were analysed using panel data regression with a random effects model. The results show that free cash flow has no significant effect on firm value, while investment opportunities have a positive and significant impact. Managerial ownership negatively and significantly affects firm value, indicating potential agency conflicts. Opportunistic managerial behaviour also negatively and substantially affects firm value, reflecting management actions prioritising personal interests. Firm size has no significant effect on firm value. This study provides insights into the optimal management of factors such as investment opportunities, ownership structure, and managerial conduct, which are crucial to enhancing firm value and shareholder interests.